Simultaneous Estimation of Levocetirizine, Ambroxol, Phenylpropanolamine and Paracetamol in Combined Dosage Forms by RP-HPLC Method - Senthamil Selvan, P.; Gopinath, R.; Saravanan, V.S.; Gopal, N. (Asian Journal of Chemistry, 2010)
A simple, selective, rapid, precise and economical reverse phase-high performance liquid chromatography (RP-HPLC) method has been developed for the simultaneous estimation of levocetirizine, ambroxol, phenylpropanolamine and paracetamol from tablets. The method was carried out on a Hichrom C18 (25 cm x 4.6 mm i.d., 5 μ) column with a mobile phase consisting of acetonitrile : 0.5% triethylamine (adjusted to pH 3.5 using orthophosphoric acid) (30 : 70 v/v) at a flow rate of 1.2 mL/min. Detection was carried out at 238 nm. Tadalafil was used as an internal standard. The retention times of phenylpropanolamine, paracetamol, ambroxol, levocetirizine and tadalafil were 2.74, 3.34, 5.09, 6.86 and 8.73 min, respectively. The validation of the proposed method was also carried out. The proposed method can be used for the estimation of these drugs in combined dosage forms.